1996
DOI: 10.1073/pnas.93.22.12155
|View full text |Cite
|
Sign up to set email alerts
|

A test of the "jigsaw puzzle" model for protein folding by multiple methionine substitutions within the core of T4 lysozyme.

Abstract: To test whether the structure of a protein is determined in a manner akin to the assembly of a jigsaw puzzle, up to 10 adjacent residues within the core of T4 lysozyme were replaced by methionine. Such variants are active and fold cooperatively with progressively reduced stability. The structure of a seven-methionine variant has been shown, crystallographically, to be similar to wild type and to maintain a well ordered core. The interaction between the core residues is, therefore, not strictly comparable with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
115
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(122 citation statements)
references
References 26 publications
7
115
0
Order By: Relevance
“…The side-chain of Leu309 in M1 is forced to move backwards to avoid steric clash. It has been suggested that the mutation Met 3 Leu at entirely buried sites can stabilize a protein through an increase in sidechain hydrophobicity and the relative advantage in entropy of ordering a less¯exible leucine sidechain in the folded structures (Gassner et al, 1996). In this study, Met233 3 Leu is the most stabilizing of all the mutants, possibly emphasizing the effects of increased hydrophobic packing and conformational entropy.…”
Section: Mutations In the Protein Hydrophobic Corementioning
confidence: 58%
“…The side-chain of Leu309 in M1 is forced to move backwards to avoid steric clash. It has been suggested that the mutation Met 3 Leu at entirely buried sites can stabilize a protein through an increase in sidechain hydrophobicity and the relative advantage in entropy of ordering a less¯exible leucine sidechain in the folded structures (Gassner et al, 1996). In this study, Met233 3 Leu is the most stabilizing of all the mutants, possibly emphasizing the effects of increased hydrophobic packing and conformational entropy.…”
Section: Mutations In the Protein Hydrophobic Corementioning
confidence: 58%
“…In T4 lysozyme, a 1.9 kcal/mol change in DDG corresponds to approximately a 5 decrease in T m . 26 Thus, the 14 decrease in T m of unbound P214A could reflect a DDG of greater than 4 kcal/mol.…”
Section: L2 0 Mutations Affect Protein Stabilitymentioning
confidence: 99%
“…For example, the apolar cores of several natural proteins have been replaced with a single type, or a random collection, of different sized apolar residues with retention of folding and/or activity. [72][73][74][75][76][77] The changes often result in a loss in stability, and also in an increase in the dynamic properties of the side chains. However, these proteins retained folded structures, suggesting that hydrophobic interactions within the protein core are not the sole contributors to native structure.…”
Section: Determinants Of the Free Energy Gapmentioning
confidence: 99%
“…Experiments in which the cores of natural proteins are repacked with a designed or randomly selected collection of hydrophobic side chains have shown that such proteins often retain a native-like structure, indicating that a variety of combinations of side chains can give rise to native folds. [72][73][74][75][76][77] It is tempting to conclude from these studies that the packing of hydrophobic side chains is not an important determinant of conformational specificity, and that only the pattern of hydrophobic and hydrophilic residues actually matters. However, only a fraction of the sequence of a protein is normally varied in these studies, and stabilizing interfacial interactions remain constant.…”
Section: Hierarchic Principles Of Protein Designmentioning
confidence: 99%